EVALUASI JARAK CENTROID PADA PEMETAAN SEKOLAH MENEGAH ATAS UNTUK PENENTUAN LOKASI PROMOSI MAHASISWA BARU MENGGUNAKAN ALGORITMA K-MEANS - Nur Aeni Widiastuti; Noor Nailie Azzat (Jurnal DISPROTEK, 2022)
Universitas ISlam Nahdlatul Ulama Jepara is one of the private universities in the district of Jepara which is located in the coastal area. Based on data obtained from the UPT section of the UNISNU Data Center, from 2016 to 2018 the number of new students experienced a less significant increase. One of the problems that arise is the inaccuracy of the region in carrying out direct promotion strategies so that student interest is reduced. The solution offered is by mapping areas/schools that have the potential to implement direct promotion strategies. The results of this study produced 3 clusters that lead to the level of Vocational High School (SMK) education. The cluster results are said to be accurate because the distance from the first student data to the first cluster center is 4, that the distance from the first student data to the second cluster center is 1 and that the distance from the first student data to the third cluster center is 1 with the evaluation used with a comparison of the BCV value = 21, 09 WCV value = 12211.29 and the ratio of both = 0.0017 with Good criteria